Scooby-doo and the legend of the vampire - Jeralds, Scott; Kasem, Casey; Messick, Don; Camp, Hamilton (Burbank, CA : Warner Home Video, 2002)
The legendary Werewolf retires so Count Dracula resorts to kidnapping Scooby-doo and his friend Shaggy to race as the Werewolf in a Monster Rally road race against other famous monsters such as Frankenstein and the Mummy.
Features: audio commentary by Scooby-Doo, Shaggy and Fred, music videos, hidden bloopers, game, trailers of other Scooby-Doo videos, interactive menus, scene access, enhanced DVD-ROM features, web events.
Voices: Don Messick, Casey Kasem, Hamilton Camp, Jim Cummings.
Not rated.
DVD Dolby digital, mono.
In English, French, or Spanish.
Closed-captioned.
Keywords: Scooby-Doo (Fictitious character) -- Drama; Video recordings for hard of hearing people; Feature films; Animated television programs